Czech Republic : Staff Report for the 2003 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2004)
The Czech economy has turned in a solid performance, and the medium-term prospects are good. The short-term outlook is positive, although downside risks are significant The outlook for low underlying inflation leaves scope for monetary policy to continue to support growth. The government's resolve to address the deterioration in the fiscal accounts has been commended. The challenge now is to implement the proposals and prepare for medium-term output. Redressing shortcomings of the judicial and legal systems is the top priority for structural reform.